Mediation effects of math axiety in relation between the father's involvement in teaching and the students' math acievement in early elementary school - Jerković, Ivona; Milovanović, Ilija (Psihološka istraživanja, 2020)
Previous studies of math anxiety in early elementary school students indicate significant negative effects on various educational outcomes, and especially on math achievement. When it comes to anxiety factors related to math learning, one of the dominant research trends is focused on analyzing the social factors of its occurrence, that is, on the behavior of parents and teachers. However, there is very little research that links fathers' behavior, the occurrence of mathematical anxiety in children, and math achievement, since mothers have mostly been examined as a parent who is more focused on their child's education and upbringing. The aim of this study was to examine the mediating role of math anxiety in the relationship between fathers' involvement in the teaching process and children's math achievement. The sample was made up of 191 students (52.9% girls) of early elementary school age (II-IV grade) with an average age of 8.78 years, and their fathers whose average age was 41 years. The research was conducted in elementary schools in Vojvodina. The results show that evaluation anxiety plays a significant role as a mediator in the relation between the father's previous positive experience with mathematics and perceived difficulties in a child's learning mathematics. Fathers' positive experiences with mathematics and perceived difficulties in a child's math learning, in addition to acting partly through math anxiety, also have a direct impact on children's math achievement.
Keywords: math anxiety; math acievement; fathers; elementary school; involvement in teaching